Analisis Dampak Gadget Pada Perkembangan Sosial Anak Kelas VI di SDN 1 Batu Nampar: Analysis of the Impact of Gadgets on Children's Social Development at SDN Batu Nampar - Sukranudin (Pendidikan Al-Gafari, 2025)
The development of science and technology is marked by the emergence of various types of features of technology that are getting newer from day to day, this development makes human lifestyle patterns more striking because the development of technology affects the human communication model. The purpose of this study was to determine the impact of gadgets on the social development of children at SDN 2 Sepit, Keruak District. This type of research uses qualitative descriptive research, while the data collection techniques used are interviews, observations, and direct documentation with informants in the field to obtain the required data. Data analysis in this study uses data reduction analysis techniques, data presentation, and drawing conclusions or verification. The results of this study are the negative impact of gadgets on the social development of children at SDN 2 Sepit, Keruak District. This impact is caused because children use gadgets too often at home without being controlled by their parents and children who are addicted to using gadgets feel that gadgets are the most interesting thing more than playing with people around them or their peers. Therefore, schools are expected to always provide activities that can facilitate children's social development when they are in the school environment. Then parents are expected to be able to control and supervise children when using gadgets at home.